Magnetic Nanoparticles: Synthesis, Protection, Functionalization, and Application - Lu, An-Hui; Salabas, E. L.; Schüth, Ferdi (Angewandte Chemie International Edition, 2007)
This review focuses on the synthesis, protection, functionalization, and application of magnetic nanoparticles, as well as the magnetic properties of nanostructured systems. Substantial progress in the size and shape control of magnetic nanoparticles has been made by developing methods such as co‐precipitation, thermal decomposition and/or reduction, micelle synthesis, and hydrothermal synthesis. A major challenge still is protection against corrosion, and therefore suitable protection strategies will be emphasized, for example, surfactant/polymer coating, silica coating and carbon coating of magnetic nanoparticles or embedding them in a matrix/support. Properly protected magnetic nanoparticles can be used as building blocks for the fabrication of various functional systems, and their application in catalysis and biotechnology will be briefly reviewed. Finally, some future trends and perspectives in these research areas will be outlined. Particularly attractive: Magnetic nanoparticles can be prepared and protected against corrosion in a variety of ways (Scheme: polystyrene (PS) coating of MnFe2O4 particles by atom‐transfer radical polymerization). The protected magnetic nanoparticles can be further functionalized for many applications including catalysis and biotechnology.